The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/bja/aes467
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of fluid responsiveness in mechanically ventilated children undergoing neurosurgery

Abstract: ClinicalTrials.gov, NCT01364103.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 30 publications
5
118
1
1
Order By: Relevance
“…However, it was controversial whether SVV changed when IAP was increased in patients undergoing laparoscopic surgery (7,8). On the other hand, noninvasive plethysmographic variability index (PVI) is a new parameter used for the purpose of fluid responsiveness in patients receiving several kinds of surgeries (9)(10)(11)(12)(13)(14). In patients undergoing laparoscopic surgery, a previous study has suggested that PVI increased significantly after pneumoperitoneum was established (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was controversial whether SVV changed when IAP was increased in patients undergoing laparoscopic surgery (7,8). On the other hand, noninvasive plethysmographic variability index (PVI) is a new parameter used for the purpose of fluid responsiveness in patients receiving several kinds of surgeries (9)(10)(11)(12)(13)(14). In patients undergoing laparoscopic surgery, a previous study has suggested that PVI increased significantly after pneumoperitoneum was established (7).…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of parameters for fluid responsiveness in pediatric patients has already been demonstrated in previous reports [5,6,7,21,22,23]. However, there was some controversy about which parameter was the most appropriate to use.…”
Section: Discussionmentioning
confidence: 94%
“…However, there was some controversy about which parameter was the most appropriate to use. In some published articles, parameters based on pressure measurements were not suitable for pediatric patients because of the different arterial elastic properties of pediatric patients compared with adult patients [6,20,21]. Therefore, parameters related with the changes of aortic blood flow and velocity as measured by echocardiographic examination were shown to be adequate for pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taikant dirbtinę plaučių ventiliaciją (DPV), šis ATV subliuškimo indeksas yra patikimas prognozuojant teigiamą atsaką į skysčius (11)(12)(13)(14). Barbier ir kt.…”
Section: Aptarimasunclassified